THE ANALYSIS OF MORPHOLOGY IN WRITING AN ENGLISH NARRATIVE COMPOSITION - Paramita Kusumawardhani (Wanastra: Jurnal Bahasa dan Sastra, 2015)
The purpose of the research is to analyze about morphology in writing an English narrative composition. Morphology is the study of morphemes which are the smallest significant units of grammar. There are two kinds of morphology, they are derivational and inflectional. Affixes such as suffixes, infixes, prefixes, ablaut and reduplication are kinds of derivational morphology, meanwhile plural, possessive, past time, progressive, comparative and superlative are kinds of inflectional morphology. Morphology mostly used in writing and writing is the most difficult part in English subject as what it is said different from what it is written. Writing is related to composition and there 4 kinds of composition, they are: argumentation, description, exposition and narration. The morphology itself sometimes gives some difficulties to the learners when they are studying about writing.  Keywords: Morphology, Derivational, Inflectional, Writing Narrative Composition